1979
DOI: 10.3133/ofr78800
|View full text |Cite
|
Sign up to set email alerts
|

Southeast Georgia embayment high-resolution seismic-reflection survey

Abstract: A high-resolution seismic survey of the offshore part of the Southeast Georgia Embayment on about a 20 km spacing was completed in 1976. A stratigraphic analyses of the data shows that the largest controlling factor in the depositional history of the shelf has been the Gulf Stream. These currents have shifted back and forth across the shelf, at times incising into shelf sediments, and at all times blocking much of the accumulation of Cenozoic sediments seaward of the Florida-Hatteras Slope. In the southern reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 2 publications
(2 reference statements)
1
27
0
Order By: Relevance
“…The Gulf Stream skirts the edge of the shelf and has affected the development of the'Florida-Hatteras Slope and Blake Plateau (Edsall, 1978). Areas of submarine erosion and scour, probably results of action by the Gulf Stream, were observed on many of the seismic records (Edsall, 1978;Dillon, 1979, 1980a).…”
Section: Geological Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…The Gulf Stream skirts the edge of the shelf and has affected the development of the'Florida-Hatteras Slope and Blake Plateau (Edsall, 1978). Areas of submarine erosion and scour, probably results of action by the Gulf Stream, were observed on many of the seismic records (Edsall, 1978;Dillon, 1979, 1980a).…”
Section: Geological Frameworkmentioning
confidence: 99%
“…Areas of submarine erosion and scour, probably results of action by the Gulf Stream, were observed on many of the seismic records (Edsall, 1978;Dillon, 1979, 1980a). Profiles along track lines 9 and 15 (from Edsall, 1978) The activity of the Gulf Stream has either removed sediments younger than Paleocene or prevented deposition of the younger sediments in large areas of the southern and middle portions of the survey area of the Florida-Hatteras Slope and Blake Plateau (Edsall, 1978). Site 34960 was located in an area where Edsall (1978) and Paull and Dillon (1979) suggested that Paleocene sediments may be exposed on the sea floor.…”
Section: Geological Frameworkmentioning
confidence: 99%
See 3 more Smart Citations